2013
DOI: 10.1177/0954411913503064
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical characterization of living and dead undifferentiated human adipose-derived stem cells by using atomic force microscopy

Abstract: In this article, to map the mechanical properties of undifferentiated human adipose-derived stem cells, local mechanical characterization is carried out on the adipose-derived stem cells. In addition, to distinguish the living and dead human adipose-derived stem cells, mechanical characterization is also implemented on both living and dead adipose-derived stem cells. In this study, Young's modulus of the cell membrane is used for representing the mechanical properties of cells. To obtain Young's modulus of cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…Atomic force microscopy (AFM) nanoindentation measures tissue mechanics with nanoscale resolution by applying a small compressive force and extracting the Young's, or elastic, modulus 13 . Only a few studies have applied AFM to cells derived from adipose tissue [14][15][16][17][18][19] , several of which attempted to directly measure mechanical properties, but none of these studies applied AFM to intact adipose tissue or investigated disease correlations. Related to this point, AFM has been utilized to investigate the mechanical properties of whole human tissues, including those from the brain 20 , eye 21 , and heart 22,23 , providing important insights for sample preparation and mechanical property analyses of our human adipose tissues.…”
mentioning
confidence: 99%
“…Atomic force microscopy (AFM) nanoindentation measures tissue mechanics with nanoscale resolution by applying a small compressive force and extracting the Young's, or elastic, modulus 13 . Only a few studies have applied AFM to cells derived from adipose tissue [14][15][16][17][18][19] , several of which attempted to directly measure mechanical properties, but none of these studies applied AFM to intact adipose tissue or investigated disease correlations. Related to this point, AFM has been utilized to investigate the mechanical properties of whole human tissues, including those from the brain 20 , eye 21 , and heart 22,23 , providing important insights for sample preparation and mechanical property analyses of our human adipose tissues.…”
mentioning
confidence: 99%
“…Deriving the mechanical properties from such stem cells will delineate important information. A clear enhancement (∼10–17 times) in Young's moduli between living and dead undifferentiated adipose‐derived stem cells was observed by Hu et al Another study demonstrated that an increased compliance of cancerous and precancerous cells may behave in a “crumble and yield” manner . This study revealed the order of Young's moduli at 1 nN stiffness of indentation force: normal squamous cells (EPC2) (4.7 kPa live and 9.9 kPa fixed) > metastatic (CP‐A) (3.1 kPa live and 2.9 kPa fixed) > dysmoplastic esophageal cells (2.6 kPa live and 2.1 kPa fixed) …”
Section: Transformation Of Normal Cells To Cancer Cellsmentioning
confidence: 51%
“…Combining CTC isolation technology and nanoindentation hybrid platform will result in high recovery rates as well as information on the state of cancers for superior diagnostics . Another group investigated nanoindentation experiments and drug–target interactions directly on patient cancer cells, which mimic human in vivo conditions . The Gaussian fit of the histogram of nanoindentation binding force of CD20‐rituximab on B‐cell lymphomas was much higher than normal cells .…”
Section: Clinical Validationmentioning
confidence: 99%
“…The vertical force of the AFM cantilever tip used to monitor changes in cardiomyocyte set at 0.4 nN. Different probing locations could lead to the variations of the measured beating forces [21]. To reduce the effect, the AFM probe was placed in the central region of the cell and ten positions were measured/averaged for each cell in the experiments.…”
Section: Characterisation Of Cardiomyocyte Contractionmentioning
confidence: 99%
“…One of the most important factors for evaluating the activities of cardiomyocytes is the mechanical contraction [18][19][20]. Atomic force microscope (AFM) technique has been widely applied in the mechanical characterisation of cells due to its high resolution on the nanoscale [21,22]. Its application on characterising the nanomechanical properties of single cells and molecules has broadened the insights into cellular structures and biology functions.…”
mentioning
confidence: 99%